2020
DOI: 10.1253/circj.cj-20-0051
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) and Cardiovascular Diseases ― Revisited ―

Abstract: Two decades ago, it was recognized that lipoprotein(a) (Lp(a)) concentrations were elevated in patients with cardiovascular disease (CVD). However, the importance of Lp(a) was not strongly established due to a lack of both Lp(a)-lowering therapy and evidence that reducing Lp(a) levels improves CVD risk. Recent advances in clinical and genetic research have revealed the crucial role of Lp(a) in the pathogenesis of CVD. Mendelian randomization studies have shown that Lp(a) concentrations are causal for different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 62 publications
0
39
0
Order By: Relevance
“…In logistic regression analysis, LDL-C, TG and other indexes have weak correlation with AS and myocardial infarction, which may be related to patients taking lipid-lowering drugs. At present, a variety of drugs have been proved to reduce LP (a) level [31,32]…”
Section: Discussionmentioning
confidence: 99%
“…In logistic regression analysis, LDL-C, TG and other indexes have weak correlation with AS and myocardial infarction, which may be related to patients taking lipid-lowering drugs. At present, a variety of drugs have been proved to reduce LP (a) level [31,32]…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that elevated plasma Lp (a) is an independent risk factor for CAD, which mainly participates in the pathophysiological process of CAD via prothrombotic/anti-brinolytic effects and promoting the deposition of cholesterol in the vascular intima [33][34][35]. On an equimolar basis, Lp (a) is more likely to cause atherosclerosis than LDL because it not only contains all proatherogenic components of LDL-C but also those of Apo (a) [13].…”
Section: Discussionmentioning
confidence: 99%
“…Lp(a) thus simultaneously inherits the atherogenic properties of apoB within LDL-C, and the thrombotic and proinflammatory characteristics of apo(a). 48 Because Lp(a) is not an enzyme or a receptor, small molecules are not able to inactivate its function. Also, Lp(a)-neutralizing mAbs would be needed in massive amounts because Lp(a) exists in high concentrations.…”
Section: Atherothrombotic and Proinflammatorymentioning
confidence: 99%